“LAUDATO SI’ UAJY”: BERAGAMA DAN BERDAMPAK BAIK BAGI LINGKUNGAN HIDUP - Pabubung, Michael (Sekolah Tinggi Kateketik dan Pastoral Rantepao (STIKPAR) Toraja, 2024)
Over an extended period, religious education was misperceived as an education for pious behavior limited to rituals and individual piety. Although this perspective is not entirely wrong, in the era of educational progress and directions, religious education, especially in higher education, must pioneer and be at the forefront in realizing integrative education, i.e., the harmony of cognitive, affective, and psychomotor aspects. Using a descriptive reflection method inspired by Laudato Si’ toward the actions of one of the groups in a Religious Education course at Atma Jaya Yogyakarta University, this article provides a descriptive picture of an affordable, plain, joyful, and environmentally oriented project-based learning in higher education.